How LCA contributes to the environmental assessment of higher order effects of ICT application: A review of different approaches. (10th May 2019) - Pohl, Johanna; Hilty, Lorenz M.; Finkbeiner, Matthias
Abstract: Information and communication technology (ICT) is often considered a technology for reducing environmental emissions by increasing energy and resource efficiencies of processes. However, due to other effects of ICT, such as rebound and induction effects, the net benefits of ICT in terms of environmental impact are by no means assured. Even though the relevance of indirect or higher order effects has become a well-known issue in recent years, their environmental assessment remains controversial. Life cycle assessment (LCA) is one of the most established environmental assessment methods for modelling the environmental effects of goods and services throughout their life cycle. Although LCA is traditionally rather product-focused, there exist also LCA-based approaches to assess higher order effects of technology replacement and optimization. This paper examines whether and how LCA case studies on environmental effects of ICT already take into account related higher order effects. A systematic review of scientific literature published since 2005 has been conducted and 25 case studies were analyzed in detail. The following research questions were addressed: i) Which products are assessed? ii) Which higher order effects of ICT are considered; and iii) how is the integration of higher order effects methodically realized? The results show that few case studies were concerned with the environmental effects of the introduction of ICT services in commerce, telework and monitoring and control. Most studies investigated the substitution of certain media with electronic devices or digital services. It was found that technology-based higher order effects, such as optimization and substitution, are usually included in the assessment by choosing comparative study designs, while user-related higher order effects, such as rebound effects and induction effects, are less often considered. For the latter effects, methodological integration was mainly provided by scenario modelling and sensitivity analysis. Overall, most studies chose an attributional LCA approach. It can be concluded from the results that, in particular, user-related effects such as rebound effects have not yet been frequently included in the environmental assessment of ICT. The identified research gaps include in particular interdisciplinary approaches on how changing use patterns can be more strongly observed in LCA. Highlights: The framework of environmental impacts of ICT is extended to include behavioral effects. There are approaches to integrate certain higher order ICT effects into LCA studies. Technology-based higher order effects are usually included in the assessment. User-related higher order effects are less often considered in the assessment. User-related effects of technological change must be taken more into account in LCA.